VLA-ALMA spectroscopic survey in the hubble ultra deep field (VLASPECS): total cold gas masses and CO line ratios forz=2-3 main-sequence galaxies - Riechers, Dominik A.; Boogaard, Leindert A.; Decarli, Roberto; Gonzalez-Lopez, Jorge; Smail, Ian; Walter, Fabian; Aravena, Manuel; Carilli, Christopher L.; Cortes, Paulo C.; Cox, Pierre; Diaz-Santos, Tanio; Hodge, Jacqueline A.; et al. (The astrophysical journal. Part 2, Letters, 2020)
Using the NSF's Karl G. Jansky Very Large Array (VLA), we report six detections of CO(J = 1 -> 0) emission and one upper limit inz = 2-3 galaxies originally detected in higher-JCO emission in the Atacama Large Millimeter/submillimeter Array Spectroscopic Survey in the Hubble Ultra Deep Field (ASPECS). From the CO(J = 1 -> 0) line strengths, we measure total cold molecular gas masses ofM(gas) = (2.4-11.6) x 10(10)(alpha(CO)/3.6)M. We also measure a median CO(J = 3 -> 2) to CO(J = 1 -> 0) line brightness temperature ratio ofr(31) = 0.84 0.26, and a CO(J = 7 -> 6) to CO(J = 1 -> 0) ratio range ofr(71) r(71) = 0.17. These results suggest that CO(J = 3 -> 2) selected galaxies may have a higher CO line excitation on average than CO(J = 1 -> 0) selected galaxies, based on the limited, currently available samples from the ASPECS and VLA CO Luminosity Density at High Redshift (COLDz) surveys. This implies that previous estimates of the cosmic density of cold gas in galaxies based on CO(J = 3 -> 2) measurements should be revised down by a factor of 2 on average based on assumptions regarding CO excitation alone. This correction further improves the agreement between the best currently existing constraints on the cold gas density evolution across cosmic history from line scan surveys, and the implied characteristic gas depletion times.
Gesehen am 08.10.2020